The White Cat - Burgess, Gelett, 1866-1951; Grefé, Will, 1875-1957 (Salt Lake City, UT : Project Gutenberg, 2015)
"The White Cat" by Gelett Burgess is a novel written in the early 20th century. The story introduces us to Chester Castle, an architect who finds himself recuperating in a mysterious house after a serious accident involving his automobile. The narrative revolves around his interactions with two intriguing women Joy Fielding, the enigmatic hostess, and Leah, her maid who both possess a captivating, complex dynamic that unfolds throughout the narrative. The opening of the book sets a vivid scene as Chester awakens in an unfamiliar room, confused and in pain. He gradually becomes aware of Joy, who has cared for him. Their initial meeting is charged with chemistry and curiosity, establishing the romantic undertones that will drive their relationship. Joy s whimsical personality and Chester s fascination with her create a playful yet mysterious atmosphere. The presence of Leah adds another layer, indicating a deeper connection between the characters that hints at themes of social dynamics and personal history. As the story progresses, the reader is left with a sense of anticipation about the unfolding relationship dynamics and the secrets that each character holds. (This is an automatically generated summary.)
Release date is 2015-05-13
Produced by Al Haines
Keywords: Multiple personality -- Fiction; Hypnotism -- Fiction